Sleeping Beauty Transposon Mutagenesis of the Rat Genome in Spermatogonial Stem Cells - Ivics, Zoltán (2010)
Since several aspects of physiology in rats has evolved to be more similar to humans than that of mice, it is highly desirable to link the rat into the process of annotating the human genome with function. However, the lack of technology for generating defined mutants in the rat genome has hindered the identification of causative relationships between genes and disease phenotypes. As an important step towards this goal, an approach of establishing transposon-mediated insertional mutagenesis in rat spermatogonial stem cells was recently developed. Transposons can be viewed as natural DNA transfer vehicles that, similar to integrating viruses, are capable of efficient genomic insertion. The mobility of transposons can be controlled by conditionally providing the transposase component of the transposition reaction. Thus, a DNA of interest such as a mutagenic gene trap cassette cloned between the inverted repeat sequences of a transposon-based vector can be utilized for stable genomic insertion in a regulated and highly efficient manner. Gene trap transposons integrate into the genome in a random fashion, and those mutagenic insertions that occurred in expressed genes can be selected in vitro based on activation of a reporter. Selected monoclonal as well as polyclonal libraries of gene trap clones are transplanted into the testes of recipient/founder male rats allowing passage of the mutation through the germline to F1 progeny after only a single cross with wild-type females. This paradigm enables a powerful methodological pipeline for forward genetic screens for functional gene annotation in the rat, as well as other vertebrate models. This article provides a detailed description on how to culturerat spermatogonial stem cell lines, their transfection with transposon plasmids, selection of gene trap insertions with antibiotics, transplantation of genetically modified stem cells and genotyping of knockout animals.